Long-term monitoring of plant diversity data in the “Montagna di Torricchio” Strict Nature Reserve, Italyb2share - EUDAT - Marco Cervellini; Leonardo Salvatori; Stefano Chelli; Federico Maria Tardella; Alessandro Chiarucci; James L. Tsakalos; Giandiego Campetella; Maura Francioni; Luciano Ludovico Maria De Benedictis; Roberto Canullo (Data in Brief)
Long-term monitoring is pivotal for the collection of data capable of unravelling spatio-temporal changes in plant diversity. Here we present a dataset including plant presence and abundance data collected using a probabilistic sampling design in the “Montagna di Torricchio” Strict Nature Reserve, central Apennines, Italy. Five surveys were conducted in 35 plots during a period spanning 22 years (2002–2024). This dataset allows for the study of plant diversity changes over space and time across different habitat types by using statistical inference based on solid sampling theory.